Fiber-Reinforced Composites in Dentistry: Enhancing structural integrity and aesthetic appeal - Alla, Rama Krishna; Sanka, Gnana Siva Sai Jaya Lakshmi; Saridena, Udaya Sri Naga Gayatri; Ramaraju, Alluri Venkata; Raju, MAKV; Mantena, Satyanarayana Raju (International Journal of Dental Materials, 2023)
This review explored the recent advancements in fiber-reinforced composites (FRCs) within the context of restorative dentistry. Dental composites have undergone significant transformations, with FRCs emerging as a groundbreaking development at the intersection of aesthetics and mechanical performance. The objective of this review is to provide a comprehensive understanding of the innovative strategies employed in FRCs to address the challenges of polymerization shrinkage, wear resistance, mechanical strength, and aesthetics. FRCs, composed of fiber reinforcements strategically aligned within a resin matrix, offer enhanced flexural strength, fracture toughness, and wear resistance, essential for the longevity of dental restorations. The review further explored the dynamic relationship between fiber alignment and restoration design, highlighting the adaptability of FRCs for varied applications, from post and core restorations to bridges and splints. Through an intricate interplay of materials science and clinical demands, FRCs have revolutionized dental composites by seamlessly integrating form and function. This review underscores the transformative potential of FRCs in restorative dentistry, shedding light on the path to enhanced clinical outcomes and patient satisfaction.